1997
DOI: 10.1029/96ja02176
|View full text |Cite
|
Sign up to set email alerts
|

Relative concentration of He+ in the inner magnetosphere as observed by the DE 1 retarding ion mass spectrometer

Abstract: Abstract. With observations from the retarding ion mass spectrometer on the Dynamics Explorer 1 from 1981 through 1984, we examine the He + to H + density ratios as a function of altitude, latitude, season, local time, geomagnetic and solar activity. We find that the ratios are primarily a function of geocentric distance and the solar EUV input. The ratio of the densities, when plotted as a function of geocentric distance, decrease by an order of magnitude from 1 to 4.5 RE. After the He + to H + density ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 34 publications
9
123
2
Order By: Relevance
“…Early studies [Horwitz et al, 1986] concluded that the ratio of helium ion density to hydrogen ion density is relatively constant. A more recent examination of the DE 1 observations [Craven et al, 1997] revealed strong statistical relationships between the heliumto-hydrogen density ratio and both geocentric distance and solar activity. On the other hand, only a weak dependence on magnetic activity and local time was observed.…”
Section: Helium Ion Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies [Horwitz et al, 1986] concluded that the ratio of helium ion density to hydrogen ion density is relatively constant. A more recent examination of the DE 1 observations [Craven et al, 1997] revealed strong statistical relationships between the heliumto-hydrogen density ratio and both geocentric distance and solar activity. On the other hand, only a weak dependence on magnetic activity and local time was observed.…”
Section: Helium Ion Densitymentioning
confidence: 99%
“…These generalizations should significantly improve the agreement between the model and observations. We demonstrate this with a comparison to in situ measurements of the helium-to-hydrogen ion density ratio by the Dynamics Explorer 1 (DE 1) satellite [Craven et al, 1997]. It should be noted that, in its present version, MSKPM is not intended to reproduce plasmaspheric morphology during the refilling process (for example, no possibility of shocks is included).…”
Section: Introductionmentioning
confidence: 99%
“…This fixed profile while not very realistic allows the outflow physics and the solar wind controlling influences to be properly isolated. Dynamic ionospheric composition [Craven et al, 1997;Gallagher et al, 1998] are now just becoming available. Future models need to incorporate dynamic changes in the ionospheric com position, but quantitative models for such changes as a function of the solar wind conditions presently do not exist.…”
Section: Multi-fluid Simulationsmentioning
confidence: 99%
“…The magnetic field amplitude can be estimated from a model, or measured with a good accuracy. The electron density and effective mass (related to composition in terms of the fractional abundance of ions present in the medium) are dependent on the geophysical situation encountered, while empirical, statistical, or theoretical models, are being elaborated (Craven et al, 1997;Gallagher et al, 2000;Pierrard and Lemaire, 2001). Actual measurements of the F lh variable in the regions explored by CLUSTER thus form a valuable data set, bringing complementary information to current models.…”
Section: Introductionmentioning
confidence: 99%